ANALISIS MANFAAT JALAN LINGKAR UTARA KOTA SENTANI TERHADAP PERKEMBANGAN DI WILAYAH SEKITARNYA - Sonya Teti Pallo; Petrus Bachtiar; Harmonis Rante (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2022)
The North Ring Road section of Sentani City is also expected to require several important things related to the principles contained in regional development. The existing synergy will improve regional economic conditions as well as several social aspects and other conveniences. With the northern ring road, it is intended to reduce the traffic load in the center of Sentani City. However, it is also hoped that the Sentani North Ring Road will have a follow-up impact on economic development and increase productivity in the surrounding area. With the existence of the North Sentani Ring Road, the development of activities, especially economic activities in the vicinity, is not yet visible, whether this economic activity is related to the social characteristics of the surrounding community that do not support regional development, so it is necessary to analyze the extent of the benefits of the road to the development of the surrounding area. The objectives to be achieved in this study are to analyze the impact of the construction of the northern ring road on infrastructure development in the surrounding area, analyze the extent to which the northern ring road affects changes in socio-economic and socio-cultural characteristics of the surrounding population, analyze the extent to which the northern ring road affects regional development surrounding. From the results of this study it can be concluded that the northern ring road has an impact on infrastructure development in the surrounding area, the socioeconomic characteristics of the population around the northern ring road have increased and socio-cultural characteristics have changed with the existence of the northern ring road of the city of Sentani and the northern ring road affect the development the surrounding area